2021
DOI: 10.1002/ejic.202001156
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition and Dielectric Response Originating from Disorder‐Order Transition in the In‐Based Organic‐Inorganic Hybrid Material [NH3(CH2)5NH3][InCl5(H2O)] ⋅ H2O

Abstract: The new organic-inorganic hybrid material [NH 3 (CH 2 ) 5 NH 3 ][InCl 5 (H 2 O)] • H 2 O (1) was successfully synthesized and the reversible phase transition with Curie temperature of 239.2 K was determined by differential scanning calorimetry (DSC) measurement. Moreover, the variable-temperature singlecrystal X-ray diffraction analyses demonstrate that the title compound crystallizes in the Pnma at 280 K. As the temperature drops below Tc, the space group of 1 transforms to the P2 1 /n. Structural analyses re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Large bandgaps, highly localized charge distributions with very high exciton binding energies, and stable exciton emission energies can be achieved for cadmium metal ions in low-dimensional organic-inorganic hybrid materials [28][29][30][31][32]. Zou et al [33] reported a new hybridized metal halide for application as a solid-state light source, namely, 2 of 19 [C 6 H 7 ClN]CdCl 3 , where C 6 H 7 ClN = 4-chloromethylpyridine cation, in which the CdCl 6 octahedron forms a corrugated 1D double-chain structure by sharing non-coplanar edges, and it exhibits white-light emission with a photoluminescence quantum yield (PLQY) of 12.3% under 345 nm UV excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Large bandgaps, highly localized charge distributions with very high exciton binding energies, and stable exciton emission energies can be achieved for cadmium metal ions in low-dimensional organic-inorganic hybrid materials [28][29][30][31][32]. Zou et al [33] reported a new hybridized metal halide for application as a solid-state light source, namely, 2 of 19 [C 6 H 7 ClN]CdCl 3 , where C 6 H 7 ClN = 4-chloromethylpyridine cation, in which the CdCl 6 octahedron forms a corrugated 1D double-chain structure by sharing non-coplanar edges, and it exhibits white-light emission with a photoluminescence quantum yield (PLQY) of 12.3% under 345 nm UV excitation.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of phase transition, the latent heat of phase transition is absorbed or released. Among them, dielectric phase transition materials can switch the dielectric constant between low dielectric state and high dielectric state under the stimulation of external temperature, and have potential applications in the fields of information storage, sensors, signal processing and storage equipment [23–35] . In the past few years, they have received great attention and became a hotspot of multifunctional materials research.…”
Section: Introductionmentioning
confidence: 99%